Implikasi Putusan Mahkamah Konstitusi Nomor 105/PUU-XXII/2024 terhadap Penegakan Hukum Pencemaran Nama Baik UU ITE: Analisis Judicial Review di Indonesia (Lembaga Pengembangan Kinerja Dosen, 2026)
The Constitutional Court Decision Number 105/PUU-XXII/2024 has significantly reshaped the legal construction of defamation provisions under the Electronic Information and Transactions Law (EIT Law), particularly by limiting the interpretation of the phrase “other persons” to natural persons (natuurlijk persoon) only. This study aims to analyze the implications of the decision on legal certainty as well as its impact on litigation practices and legal protection for legal entities in Indonesia. This research employs a normative juridical method using statutory and conceptual approaches. The findings indicate that the decision enhances legal certainty by clarifying previously ambiguous norms that often led to the criminalization of freedom of expression. However, the restriction of legal subjects has shifted the legal protection mechanism for legal entities from criminal to civil remedies under Article 1365 of the Civil Code. This shift poses challenges in terms of effectiveness, particularly due to more complex litigation processes and the lack of deterrent effect compared to criminal sanctions. Therefore, a balanced approach is required between protecting freedom of expression and safeguarding institutional reputation, alongside strengthening regulations and public legal awareness to achieve justice, legal certainty, and legal utility.